Corak Maqashidi dalam Tafsir Alquran - Hamdani Anwar (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
Maqashidiis a theory that contains the values and goals which the aim of Allah rules is derived. The theory which is an important part of the study of the science of Ushul fiqh, is also developed in the Qur’anic commentary, so its interpretation based on the purpose of establishing the Shari’a (maqashid asy-syari’ah), has been able to produce a contextual interpretation, exposing the universal meaning of the Qur’an and minimize the dissent that always exists in interpretation. The Attempts in aligning the information from the Qur’an with the purpose of the Shari’a (maqashid asy-syari’ah)like this is a worth appreciation activity, given the function of the Qur’an as a guide for the welfare of humanity. This paper introduces the interpretation of Maqashidiwhich is expected to provide understanding to the Muslims of the importance of tafsir maqasidiat this time.